Validation of pulse oximetry during progressive normobaric hypoxia utilizing a portable chamber - Kolb, J. C.; Farran, P.; Norris, S. R.; Smith, D.; Mester, J. (Canadian Journal of Applied Physiology, 2004)
Validation of pulse oximetry in commercially available normobaric hypoxic chambers (NHC) has not been previously reported. The present study examined the validity of pulse oximetry (SpO2) against direct measurements of arterial oxygen saturation (SaO2) via co-oximetry (AVOXimeter 4000) in 13 young adults age 21.3 +/- 0.6 years. Over a period of 2.5 hrs, the inspired fraction of oxygen inside a NHC (Hypoxico, Inc.) was progressively reduced from 20.9% to 11.5%. Measurements of SaO2 at baseline and at 15, 30, 60, 90, 120, and 150 min during the hypoxic exposures were compared with SpO2 estimates of oxygen saturation (Nellcor 295) using reflectance (RS-10, temporal) and transmission (D-25, finger) sensors. Regression analysis and methods for assessing agreement (bias, b; precision, p) of SaO2 with SpO2 were similar (R2 = 0.92, 0.89; b = 0.016, -0.47; p = 2.47, 3.03; RS-10 and D-25, respectively). When SaO2 < 85%, RS-10 had greater validity than D-25 (R2 = 0.73, 0.56; b = 1.38, 1.13; p = 2.72, 4.34; RS-10 and D-25, respectively). In light of these findings, caution should be exercised when monitoring individuals with pulse oximetry during desaturation episodes below 85%. When employing frequent NHC exposures, a priori validation of SpO2 utilized to assess blood oxygen status appears warranted.